Acceptability and feasibility of wearing activity monitors in community‐dwelling older adults with dementia. (20th February 2019) - Farina, Nicolas; Sherlock, Gina; Thomas, Serena; Lowry, Ruth G.; Banerjee, Sube
Abstract : Objectives: Measuring physical activity is complicated particularly in people with dementia, where activity levels are low and subjective measures are susceptible to inaccurate recall. Activity monitors are increasingly being used within research; however, it is unclear how people with dementia view wearing such devices and what aspects of the device effect wear time. The aim of the study was to evaluate the acceptability and feasibility of people with dementia wearing activity monitors. Methods: Twenty‐six, community‐dwelling, people with mild dementia were asked to wear an activity monitor (GENEactiv Original) over a 1‐month period. Perceptions of the device were measured using the Quebec User Evaluation of Satisfaction with Assistive Technology (QUEST) 2.0, alongside qualitative interviews. Device diary and activity monitor data were used to assess compliance. Results: Participants tended to find wearing the activity monitors acceptable, with only three participants (12%) withdrawing prior to the study end date. Participants were generally satisfied with wearing the devices as measured by the QUEST (Mdn = 4.4, IQR = 1.1). Four themes were identified that influenced perceptions of wearing the device: external influences, design, routine, and perceived benefits. Discussion: Asking people with dementia to wear a wrist‐worn activity monitor for prolonged periods appears to be both feasible and acceptable. Researchers need to consider the needs and preferences of the sample population prior to selecting activity monitors.